Using biomaterials to improve mesenchymal stem cell therapies for chronic, nonhealing wounds - Romina Keshavarz; Sara Olsen; Bethany Almeida (Wiley, 2024)
Abstract Historically, treatment of chronic, nonhealing wounds has focused on managing symptoms using biomaterial‐based wound dressings, which do not adequately address the underlying clinical issue. Mesenchymal stem cells (MSCs) are a promising cell‐based therapy for the treatment of chronic, nonhealing wounds, yet inherent cellular heterogeneity and susceptibility to death during injection limit their clinical use. Recently, researchers have begun to explore the synergistic effects of combined MSC‐biomaterial therapies, where the biomaterial serves as a scaffold to protect the MSCs and provides physiologically relevant physicochemical cues that can direct MSC immunomodulatory behavior. In this review, we highlight recent progress in this field with a focus on the most commonly used biomaterials, classified based on their source, including natural biomaterials, synthetic biomaterials, and the combination of natural and synthetic biomaterials. We also discuss current challenges regarding the clinical translation of these therapies, as well as a perspective on the future outlook of the field.